Donas de casa, criadas e empregadas: trabalho doméstico na Fortaleza dos anos 1920 e 1930 - Pascoa, Michelle Arantes Costa (2020)
This master thesis aims to analyse the domestic labour carried out by housewives, foster daughters and employees in the city of Fortaleza, in the 1920s and 1930s. This period was marked by an increase in population due to migratory flows of people who fled from droughts that affected the interior of the state. This was related to an accelerated urbanization process, encouraging doctors and sanitarians to mobilize women to exercise cleaning and hygiene practices. Here, it is discussed a femininity produced in and by domestic work, punctuating qualities expected from each domestic worker, as well as deviations in conduct and its consequences. In addition, this work brings to light the problem that, through discursive battles, sought to naturalize domestic work as inherent to the female biology. Averse to this, it will be demonstrated that the exercise of domestic work is not natural, but it is forged through training and learning. Mobilizing national agendas – from training women to domestic work – to their interests, coordinated actions by feminists who fought for girls to have access to education will be presented. For this purpose, dictionaries, criminal proceedings, hemerographic sources and local bibliography were used as historical sources, trying to understand the meanings attributed to the word ―domestic‖ and how this term was applied in other traces.